2019
DOI: 10.1186/s40425-019-0650-9
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome affects the response to anti-PD-1 immunotherapy in patients with hepatocellular carcinoma

Abstract: Background Checkpoint-blockade immunotherapy targeting programmed cell death protein 1 (PD-1) has recently shown promising efficacy in hepatocellular carcinoma (HCC). However, the factors affecting and predicting the response to anti-PD-1 immunotherapy in HCC are still unclear. Herein, we report the dynamic variation characteristics and specificities of the gut microbiome during anti-PD-1 immunotherapy in HCC using metagenomic sequencing. Results Fecal samples from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
335
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(356 citation statements)
references
References 26 publications
17
335
4
Order By: Relevance
“…The liver does not harbour a known intrinsic microbiome but the gut microbiota plays a critical role in liver inflammation, chronic fibrosis, liver cirrhosis and HCC development via the gut-liver axis [168][169][170]. A pilot study of 8 HCC patients treated with PD-1 inhibitors has revealed taxonomic diversity and enrichment in 20 species including Akkermansia and Ruminococcaceae to predict for response [171] suggesting characteristic alterations in the gut microbiota profile to have potential as predictive biomarkers of clinical benefit in ICPIrecipients. The precise molecular mechanisms that may facilitate anti-tumour immunity warrant further elucidation in larger cohorts.…”
Section: Tumour Mutational Burden (Tmb)mentioning
confidence: 99%
“…The liver does not harbour a known intrinsic microbiome but the gut microbiota plays a critical role in liver inflammation, chronic fibrosis, liver cirrhosis and HCC development via the gut-liver axis [168][169][170]. A pilot study of 8 HCC patients treated with PD-1 inhibitors has revealed taxonomic diversity and enrichment in 20 species including Akkermansia and Ruminococcaceae to predict for response [171] suggesting characteristic alterations in the gut microbiota profile to have potential as predictive biomarkers of clinical benefit in ICPIrecipients. The precise molecular mechanisms that may facilitate anti-tumour immunity warrant further elucidation in larger cohorts.…”
Section: Tumour Mutational Burden (Tmb)mentioning
confidence: 99%
“…Remarkably, the influence of the gut microbiota composition in modulating tumor responses to immunotherapy has also been reported in various cancers such as melanoma, lung and kidney cancer. This effect was observed in different geographic regions where microbiota might differ (North America, Europe, East Asia) (4,(73)(74)(75). Reconstitution of germ-free mice with fecal material from lung cancer immunotherapy responders led to increased T-cell responses, and greater efficacy of anti-PD-1 therapy (4).…”
Section: Supplementation Of a Muciniphila In The Context Of Metabolimentioning
confidence: 99%
“…455 Therefore, there is an urgent need to combat therapeutic resistance and identify biomarkers that can be used to predict the response to ICIs. The high heterogeneity to ICI therapy in cancer patients can be partially explained by differences in gut microbiome composition, with compelling evidence suggesting that gut microbiome and even specific key bacterial taxa potentially contribute to interindividual variation in ICI therapeutic efficacy in numerous clinical cohorts [456][457][458][459][460] and that optimal modulation of the gut microbiome is sufficient to strengthen the therapeutic response to ICIs in preclinical models. 43,461,462 The particular gut microbiome seemingly has a positive influence on the effectiveness of ICIs via manipulating the tumor microenvironment in preclinical models.…”
Section: Microbiome-mediated Effects On Cancer Immunotherapymentioning
confidence: 99%
“…459 Similarly, the gut microbiome potentially exerts a profound effect on the responses of HCC patients receiving anti-PD-1 mAb. 456 Responders exhibit greater taxa richness and 20 responder-enriched species (such as A. muciniphila and Ruminococcaceae spp.) that are associated with carbohydrate catabolism and methanogenesis.…”
Section: Microbiome-mediated Effects On Cancer Immunotherapymentioning
confidence: 99%